ORAL HEALTH STATUS AND BEHAVIOR OF TUNAS HARAPAN ELEMENTARY SCHOOL STUDENTS - Theresia, Tiarma Talenta; Lestari, Sri; Asia, Raden Roro Asyurati; Kissanti, Wahyu Ari (Jurnal Kesehatan Tambusai, 2024)
Caries can be caused by a lack of knowledge that shapes attitudes and behavior of neglecting oral hygiene. Caries is the main problem that is often found in children. To increase knowledge of the importance of dental and oral health in children, an approach was made through the UKGS program fostered by the Puskesmas. It is hoped that this survey result will serve as material for evaluating UKGS activities for Puskesmas and schools. Objective of this research is To determine the oral health status and behavior of SDS Tunas Harapan students. A survey with a cross-sectional design was conducted among students in grades I-VI at SDS Tunas Harapan. Data collection used the def-t index, DMF-T, OHIS, and a behavioral questionnaire. Data analysis used the univariate method and presented in tabular form. The average value of def-t is 4.6, DMF-T is 1.3, and OHIS is good (58%), fair (38%), bad (4%). The results of filling out the questionnaire showed good knowledge (86%), moderate (14%) and less (0%). Good attitude (92%), moderate (8%) and less (0%). Practice is good (72%), moderate (28%) and less (0%). A total of 109 SDS Tunas Harapan students had dental caries (87%) out of a total of 128 students who attended the examination.